1981
DOI: 10.1139/v81-060
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the generation of free hydroxyl radicals from certain quinone antitumor antibiotics upon reductive activation in solution

Abstract: This paper is dedicated to Prof. Raymond U . Lemieux on the occasion of his 60th birthday J. WILLIAM LOWN and HSIAO-HSIUNG CHEN. Can. J. Chem. 59,390 (1981). The nature of the reactive oxygen species generated from certain quinone antitumor antibiotics upon reductive activation in aqueous solution was investigated. A kinetic criterion was employed involving the relative rate of trapping of hydroxyl and formate radicals by the spin-trap 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) in conjunction with epr spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 14 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…6C and 7C). Because the anion formate is known to readily access the catalytic site of SOD, this further indicates that most of the DMPO-OH obtained in the absence of scavengers emanate from a mechanism other than the reaction of free ⅐ OH with DMPO (35,37). Furthermore, the overall spin adduct concentration was enhanced by 30 -40% at 20 mM formate and by 350 -400% at 200 mM formate (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…6C and 7C). Because the anion formate is known to readily access the catalytic site of SOD, this further indicates that most of the DMPO-OH obtained in the absence of scavengers emanate from a mechanism other than the reaction of free ⅐ OH with DMPO (35,37). Furthermore, the overall spin adduct concentration was enhanced by 30 -40% at 20 mM formate and by 350 -400% at 200 mM formate (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…5B). Although the formation and decay kinetics of the two adducts are reported to be similar, a ratio of 1,400 was required to reach a DMPO-Et/DMPO-OH ratio of 1 (34,35,37). In contrast, with a ⅐ OH generating system the ratio of these adducts should be similar to the ratio of [EtOH]/[DMPO].…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have shown that reductive cycling to give the semiquinone, and the presence of O2 and H202 are important [3][4][5]7], and there is some evidence for protection by superoxide dismutase [ 1,2]. Decreased cytotoxicity in high pressure O2 has also been observed [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that these processes depend on the production of 0, and Ha02 from the reaction of the adriamycin free radical (Adr') with 02, with subsequent formation of OH. radicals [2,3,5,6]. However, it is not yet clear how 0, produced in biological systems can give rise to OH' radicals [9-l 11.…”
Section: Introductionmentioning
confidence: 99%
“…In order to place its involvement in lipid peroxidation in a reasonable chemical setting, it has been presumed that the semiquinone is competent for the reduction of alkyl peroxides to the hydroxyl radical (37,38). Indeed, spin-trapping experiments are consistent with this notion (38,39). Direct evidence for this reaction has been provided by Kalyanaraman et al (40), where the effect of H202 on the steady state semiquinone concentration during enzymatic reduction has been used to estimate a bimolecular rate constant of about 103-104 M-1sec-1 for this reaction.…”
Section: Chemistry Of the Anthracycline Semiquinonementioning
confidence: 99%